Neighbourhood green space and health disparities in the global South: Evidence from Cali, Colombia. (November 2021) - Hong, Andy; Martinez, Lina; Patino, Jorge E.; Duque, Juan C.; Rahimi, Kazem
Abstract: Increasing attention has been given to the role of green space in reducing health disparities. However, robust evidence to support decision making is lacking in the global South. We investigate the relationship between green space and health as well as its underlying mechanism in Cali, Colombia. Results indicate that neighbourhood greenness is associated with enhanced self-rated 'good' health and reduced physical and mental distress. The health benefits of green space appear to be stronger for people living in wealthier neighbourhoods than those in poor neighbourhoods. Results highlight the importance of considering health disparities for future green infrastructure planning in the global South context. Highlights: Green space is positively associated with self-rated health in Cali, Colombia. Physical activity may be an underlying mechanism linking green space to health. The more green space does not mean the better if socioeconomic inequalities in health exist. Health disparities should be considered for green space planning in the global South context.